Adaptasi Santri Generasi Z Di Pondok Pesantren Darul Lughoh Wadda’wah (Bangil, Pasuruan Jawa Timur) - Muhammad Fredy Kurniawan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Generation Z students face many factors when adjusting to the Darul Lughoh Wadda'wah Islamic boarding school. These factors include changes in lifestyle, technology, social relations, the physical environment of the peasantry, and academic and religious demands. Generation Z students show flexibility and the ability to adapt well in the Islamic Boarding School environment even when facing certain challenges. The purpose of this study was to examine the adaptation of Generation Z students at the Darul Lughoh Wadda'wah Islamic boarding school in Bangil, Pasuruan, East Java. It is important to understand the adaptation of Generation Z students because they are different from previous generations and face challenges in the context of Islamic boarding schools. The research method used is a qualitative approach with data collection techniques in the form of in-depth interviews and participatory observation.